2017
DOI: 10.1080/21681805.2017.1295101
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of narrow-band imaging in flexible cystoscopy: the DaBlaCa-7 study

Abstract: NBI can be a useful tool in clinical decision making as a supplement to WL because it yields a significantly higher detection rate than WL cystoscopy alone. This is particularly relevant in patients with known recurrent NMIBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…A multicenter study published by Drejer et al [ 23 ] in 2017 showed that NBI had higher sensitivity than WLC, and changed the relevant clinical decision in 18 cases (1.9%). In this study, 1 additional cancer (CIS) was detected using NBI in 1 patient (1.18%, 1/85).…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study published by Drejer et al [ 23 ] in 2017 showed that NBI had higher sensitivity than WLC, and changed the relevant clinical decision in 18 cases (1.9%). In this study, 1 additional cancer (CIS) was detected using NBI in 1 patient (1.18%, 1/85).…”
Section: Discussionmentioning
confidence: 99%
“…Narrow Band Imaging (NBI) verschärft den Kontrast zwischen hypervaskularisiertem Gewebe (im Regelfall Tumor) zur normalen Blasenschleimhaut. Eine verbesserte Detektion im Vergleich zur WL-Zystoskopie konnte sowohl für die flexible Zystoskopie als auch für die TUR‑B gezeigt werden [ 29 , 30 , 31 , 32 ]. Eine verringerte Rezidivrate bestätigte sich nur für die Subgruppe der Low-risk-Tumoren nach 3 und 12 Monaten [ 33 ].…”
Section: Erweiterte Techniken Der Tumorvisualisierungunclassified
“…NBI enhance the contrast between the superficial mucosa and microvascular structures via only emitting two bandwidths of illumination, 415 nm (blue) and 540 nm (green) ( 18 , 19 ). Assisted by specialized cystoscopes, surgeons could notice abnormal microvasculature and perform NBI-guided TURBT without prior instillation of dyes ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous systematic review and meta-analysis suggested that novel visualization methods assisted TUR (VA-TUR) by PDD or NBI can improve cancer detection and decrease the risk of BC recurrence in the short and long term, compared with white light ( 20 , 21 ). VA-TUR have been recommended as weak evidence in the latest European Association of Urology Guidelines on NMIBC ( 22 ).…”
Section: Introductionmentioning
confidence: 99%